They lifted me into the sun again and packed my skull with cinnamon - Dodge, Jason (Kodoji Press, 2023)
They lifted me into the sun again and packed my skull with cinnamon is a new artist's book by Jason Dodge. The book, composed entirely of images of bells, relates to a work in the Magic Megève collection in which bells tuned to 440 hz were mounted inside of every wall of the chalet. This is his first publication with Archivorum × M and Kodoji Press. Jason Dodge (born in 1969, Pennsylvania) lives on Møn, has shown work internationally in solo and group exhibitions. In his installations, which in their simplicity seem to contradict their conceptual nature, Dodge communicates powerful narratives. Literature is an important stimulus for Dodge’s work. But rather than specific novels or poems, it is the act of writing itself – the application of ink to paper – that sparks certain ideas. In a similar process, the objects in his works present themselves to the viewer as words of a story. Yet the story is never linear; it opens up different spaces of association for different people
Sämtliche Titelangaben vom Lesebändchen übernommen
Keywords: Künstlerbuch; Dodge; Jason; Glocke